The Application of Botulinum Toxin in Oral and Maxillofacial Surgery - Nilesh, Kumar; Patil, Monica (Cambridge Scholars Publishing, 2022)
The application of botulinum toxin has seen tremendous growth in the past decade. From being a bacterial toxin and one of the most lethal food poisons known to mankind, and later exploited as a biological weapon, botulinum toxin is currently one of the most versatile pharmaceutical agents used in medicine. The toxin finds a plethora of clinical applications in the fields of ophthalmology, neurology, dermatology, dentistry and oral and maxillofacial surgery. The use of botulinum toxin in the field of oral and maxillofacial surgery has been continuously evolving, for aesthetic and functional ind.